Tzanaki’s Score Vs Modified Alvarado’s Score In Diagnosing Acute Appendicitis: A Comparative Study In A Tertiary Care Hospital - Rajpura, Ashok Kumar; Choudhary, Dharmendra; Khorwal, Bhagchand; Bhutra, Shyam; Yadav, Dinesh Kumar; Bansal, Kamal (Journal of Society of Surgeons of Nepal, 2023)
Introduction: Acute appendicitis is commonly diagnosed when a patient presents with pain in right iliac fossa. Various Scoring systems are used to diagnose acute appendicitis and mainly include the presenting signs and symptoms, but are not acceptable for patients. The purpose of this study was to assess effectiveness of modified Alvarado score and Tzanaki’s Score in the diagnosis of acute appendicitis. Methods: A prospective observational study was done in department of General Surgery JLN Medical College Hospital, Ajmer which incorporated 200 patients presenting with the signs and symptoms of acute appendicitis. Patients were evaluated by Modified Alvarado score and Tzanaki’s Score during admission and based on the treating surgeon’s decision, were operated. Finally, the score was compared with the diagnosis done by histopathological examination of the operated specimen. Results: The sensitivity & specificity of Modified Alvarado Score was 84.26% & 72.7% respectively with a positive predictive value of 96.15% & negative predictive value of 36.3%. The sensitivity and specificity of Tzanaki’s score was 88.2% and 72.7% respectively with a positive predictive value of 96.31% and negative predictive value of 43.24%. The diagnostic accuracy of Alvarado score was 83% and that of Tzanaki’s score was 86.5%. Conclusion: Tzanaki’s scoring system can be used as an effective modality in the diagnosis of acute appendicitis. There is increased sensitivity and diagnostic accuracy in Tzanaki’s scoring when compared to modified Alvarado score.